Cation and anion effect on the biodegradability and toxicity of imidazolium– and choline–based ionic liquids. (February 2020) - Mena, I.F.; Diaz, E.; Palomar, J.; Rodriguez, J.J.; Mohedano, A.F.
Abstract: This work studies the effect of the cation and anion on the biodegradability and inhibition of imidazolium– and choline–based ionic liquids (ILs) using activated sludge. Six commercial ILs, formed by combination of 1–Butyl–3–methylimidazolium (Bmim + ) and N, N, N–trimethylethanolammonium (Choline + ) cations and chloride (Cl − ), acetate (Ac − ) and bis(trifluoromethanesulfonyl)imide (NTf2 – ) anions were evaluated, all representative counter–ions with markedly different toxicity and biodegradability. Inherent and fast biodegradability tests were used to evaluate both the microorganism inhibition and the IL biodegradability. In addition, the ecotoxicological response (EC50 ) of the ILs was studied using activated sludge and Vibrio fischeri (Microtox® test). Bmim + and NTf2 – can be considered as non–biodegradable, whereas aerobic microorganisms easily degraded Choline + and Ac − . The biodegradation pattern of each cation/anion is nearly unaffected by counter–ion nature. Moreover, concentrations of CholineNTf2 higher than 50 mg/L caused a partial inhibition on microbial activity, in good concordance with its low EC50 (54 mg/L) measured by respiration inhibition test, which alerts on the negative environmental impact of NTf2 –containing ILs on the performance of sewage treatment plants. Graphical abstract: Image 1087 Highlights: Bmim + and NTf2 – were non-biodegradable constituents of ILs. Choline and acetate are ideal components of a biodegradable IL. Choline + was slightly less toxic than Bmim + . IL's toxicity is drastically increased by incorporation of NTf2 – .